IMPLEMENTATION, OBJECTIVES, PRINCIPLES, MODULES AND THEIR CHARACTERISTICS OF ELECTRONIC GOVERNMENT - Erkinov Ilkhomjon Elmurodjon ogli (Scholar Express Journals, 2022)
The article describes the development of electronic government, its importance in optimizing relations between the state and citizens. Also, the three main modules of e-government and the stages necessary for effective operation of e-government, the main goals of e-government and the main principles of e-government in the implementation of these goals were analyzed on a scientific basis. Also, the practical results of electronic government in our country in 2017-2022 have been systematically shown.
Keywords: government; public services; e-participation; e-democracy